Micro-Political Risk Factors for Strategic Alliances: Why Machiavelli's Animal Spirits Matter. (October 2014) - Marshall, Alasdair; Ojiako, Udechukwu; Chipulu, Max
Sociological perspectives on strategic alliances between firms are heavily influenced by economic theory. As such, they regard alliance entry, maintenance and exit decisions as following calculative rationalities concerned with the consequences for access to resources and transaction costs. Our theoretical article offers a contrasting sociological perspective whereby 'animal spirits' trump these calculative rationalities as factors in alliance decision making. Using Machiavelli's well-known psychological realism, we explain how 'vulpine' and 'leonine' animal spirits can shape psychological and cultural contexts for the micro-political aspects of alliance decision making. This enables us to specify micro-political risk factors related to very common psycho-cultural differences, which we think all firms that forge alliances across cultural distance should consider.